Method to solve qualitative experimental tasks in biology - García, Dayly; Guerra, Yusimí; Leyva, Julio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The problem of the low cognitive independence of the students when performing laboratory practices in biology is addressed. To mitigate it, it is proposed to transform traditional laboratory practices into experimental tasks and to introduce a method to guide students in the independent solving of qualitative experimental tasks in biology. The method was obtained by analogy. For the validation of the proposal, a model experiment and a practical intervention were carried out following an opening sequence in a sample of students from the Bachelor of Education, Biology career. From the statistical point of view, a randomized complete block design was applied to compare the cognitive independence of the students in the different stages of the solving method, and of the students among themselves. As a result of the model experiment, the functionality of the method for the design of the experimental tasks corresponding to the biological disciplines was evidenced. In the practical intervention, didactic regularities were detected, which allowed obtaining significant advances in the cognitive independence of the students in the sample.